Exploring the Complexity of How Families Are Engaged in Early Speech-Language Pathology Intervention Using Video-Reflexive Ethnography - Melvin, Katelyn; Meyer, Carly; Scarinci, Nerina (International journal of language & communication disorders, 2021)
Background: Despite being an important aspect of effective early intervention service delivery, 'engagement' has been inconsistently defined in paediatric healthcare. Previous research has identified that engagement in early speech-language pathology intervention is complex and multifaceted. However, more research is needed to understand the ways that different families may engage with intervention in different settings. Aims: To explore the complexity of engagement in early speech-language pathology intervention from the perspectives of both families and their speech-language pathologists (SLPs). Method & Procedures: Video-reflexive ethnography was used to explore engagement with 21 matched SLP-family dyads in early intervention services. Up to three intervention appointments for each participating family were video recorded. Short video segments were selected and played to participants during individual semi-structured interviews where participants were invited to reflect on the interactions captured (i.e., 'video-reflexive sessions'). Interview data were analysed using thematic analysis. Outcomes & Results: Results from the interview data were organized into one overarching theme 'Families may have "different levels of engagement"', and four individual themes that reflected how families engage differently in various aspects of intervention, including (1) attending sessions and coming into the room; (2) actively participating in sessions; (3) continuing to actively participate outside sessions; and (4) having open and honest communication with their SLPs. Conclusions & Implications: Families may have different levels of engagement in various aspects of intervention, which contribute to their unique profile of engagement. Findings of this study prompt SLPs to move beyond using blanket statements about "whether or not" families are engaged, to instead describing in detail "how" families are uniquely engaged.